2013
DOI: 10.1186/1471-2458-13-873
|View full text |Cite
|
Sign up to set email alerts
|

A school intervention for mental health literacy in adolescents: effects of a non-randomized cluster controlled trial

Abstract: Background“Mental health for everyone” is a school program for mental health literacy and prevention aimed at secondary schools (13–15 yrs). The main aim was to investigate whether mental health literacy, could be improved by a 3-days universal education programme by: a) improving naming of symptom profiles of mental disorder, b) reducing prejudiced beliefs, and c) improving knowledge about where to seek help for mental health problems. A secondary aim was to investigate whether adolescent sex and age influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
105
1
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(127 citation statements)
references
References 37 publications
10
105
1
11
Order By: Relevance
“…11 In the present study four fifth of the students singled out psychiatrist as the most reliable help for the patients from all of the professional groups. Similar findings were found in other studies 15,26,16,17,11,27 which revealed that, among the professional helpers most frequently consultation with a psychiatrist was preferred by the majority for depression and depression. Immediate community members like close friends, neighbors, family and self help group were endorsed to be helpful by most of the previous studies 13,9,4,11 and the same was consistent with the present study findings.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…11 In the present study four fifth of the students singled out psychiatrist as the most reliable help for the patients from all of the professional groups. Similar findings were found in other studies 15,26,16,17,11,27 which revealed that, among the professional helpers most frequently consultation with a psychiatrist was preferred by the majority for depression and depression. Immediate community members like close friends, neighbors, family and self help group were endorsed to be helpful by most of the previous studies 13,9,4,11 and the same was consistent with the present study findings.…”
Section: Discussionsupporting
confidence: 80%
“…Immediate community members like close friends, neighbors, family and self help group were endorsed to be helpful by most of the previous studies 13,9,4,11 and the same was consistent with the present study findings. More than one third of the students had opinion that dealing with the problem alone could be helpful for depression, which is similar as the results of two mental health literacy studies 28,16 that approximately half of the sample were of the view that 'dealing with the problem alone' is a helpful strategy. In present study a local doctor was reported to be helpful by over one third of the students which is contradictory to other studies 4,11,21 which local doctors or general practitioners were judged to be most helpful by majority of participants rather than psychiatrist, one of the reason for this difference can be the disparity of the concept of 'family doctor' which is not common in India unlike other countries.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Many do not recognize when they are experiencing symptoms. 113 An educational component on psychological health should be developed for presentation to student-athletes, coaches, and parents. This educational component may include information from this consensus statement regarding the prevalence of psychological concerns in adolescents, stressors unique to secondary school student-athletes, behaviors to monitor, and the school district's policy on referring students for psychological evaluation.…”
Section: Educationmentioning
confidence: 99%
“…The concept of MHL has been developed to fill this gap in the education system [2,13]. Our literature search identified one school MHL intervention in Norway [15] that embedded MHL into schools that demonstrated impact on student knowledge for identification of certain mental disorders and attitude changes; however, these approaches have often been input into schools by external providers and, therefore, may not lead to sustained and enhanced MHL capacity embedded into educational systems. Nor, if external providers are used, do those interventions demonstrate the positive impact on teacher mental health literacy that is seen with curriculum resource approaches delivered by teachers such as those described below.…”
mentioning
confidence: 99%